Cultura impresa y cultura política en Colombia, 1920-1946 (2022)
The research explores the relationship between political culture and print culture in Colombia between 1920 and 1946. In this period liberals, conservatives, socialists and communists found in the production, circulation and consumption of print a scenario that defined their ways of doing and acting in public life. Following the approach of material history of the political, the materiality, sociability and spatiality of the communication circuit of the printed matter in which typographers, editors, announcers, booksellers and readers intervene are reconstructed. From this perspective, the materiality of the production of the graphic arts industry and the participation of different traditions of the national political culture in its modernization process are reconstructed. In light of the definition of the contexture of the typographic industry and the development of capitalism of the printed matter in Colombia, the different printed supports that were used are explored: books, newspapers, magazines and a wide range of ephemeral items such as almanacs, brochures, billboards and advertising posters that have not been considered with sufficient attention by local historiography. Likewise, some print trade spaces are reconstructed, such as bookstores and a varied set of reading practices that are defined by the material characteristics of printed matter and the multiplication of sociability spaces that range from town houses, public squares, streets and modern public transport systems. All these elements warn new ways to think about the configuration of political modernity and the ways of participating in the public sphere in which literate and non-literate interact and define the meaning of politics in the study period.